Analisis Perbandingan Biaya Transportasi Pengiriman Barang antara Metode FIFO dengan Stepping Stone dan Vogel - Budi Gunawan; Sulistiono Wreksodihardjo (Universitas Bunda Mulia, 2017)
Transportation cost analysis appears in a number of design in various fields such as network supplies, communications networks, and variety of other fields which have the principle of transferring the object from one place to another place. This transportation cost analysis can be used as indicators or benchmarks to measure whether the usual method of delivery of goods made by certain parties were optimal or not. Application of the method of transportation cost analysis in this study is to combine several tools or methods of solving the transportation problem, which consists of the methods of the North West Corner (NWC), Stepping Stone (SS), Vogel Approximation Method (VAM). From the results of the comparison between the usual calculation of the cost paid by the company (First In First Out) with a method of solving transportation problems, will be selected that contributed the largest savings as a final result.Keywords: North West Corner, Stepping Stone, Vogel Approximation Method